(untitled) (The International Journal of Educational Sciences and Arts, 2024)
The aim of the research is to submit a proposal to include the speaking and writing skills of the STEP English language test according to the standards of Evaluation of the Common European Framework of Reference in the of Vision 2030 Saudi Arabia’s, the researcher followed the descriptive quantitative approach to achieve this goal and a list of the criteria of the Common European Framework of Reference was prepared. Speaking and writing skills, the researcher prepared a questionnaire that included these standards to ensure their availability among learners after conducting the STEP test, In addition to learners’ opinions on improving their speaking and writing skills if these two skills are included in the test, The questionnaire was applied to a random sample of learners who underwent the STEP test and their number was (153) learners, Based on the researcher’s findings, which were that the speaking and writing skills of the learners were not affected after the test, and the support of most learners Those who took the test in addition to speaking and writing skills and that this will contribute to improving their language and writing skills, It recommended the following recommendations: Seeking to include speaking and writing skills to test English language competencies in accordance with the evaluation of international standards, including For languages due to their flexibility and comprehensiveness, in addition to recommending teachers to seek to develop writing and speaking skills using various teaching methods Evaluate learners’ participation and activities immediately to motivate learners and increase their appetite for learning English, and try to link English language learning to the reality of learners, And clarify the importance of the English language in order to achieve Vision 2030 and its importance for the integration of teachers in the labor market in addition to their integration into international universities.